Extreme Early-Age Flowering of a Tali Palm (Corypha Taliera Roxb.) Tree - Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2021)
Abstract not available Bangladesh J. Plant Taxon. 28(2): 451-453, 2021 (December)